Are Digital Classrooms (i.e. PowerPoint presentations) the Only Option in Education? A Critical Discourse Analysis. - Sapkota, Chet Narayan (Madhyabindu Journal, 2025)
As educational institutions struggle with the consequences of incorporating digital technology into conventional frameworks, the discourse surrounding the digitalization (i.e. using PowerPoint presentations) of education has grown more critical. This shift's potential benefits and drawbacks must be considered to assess whether PowerPoint presentations have "sold out" in the educational system. This study examines the discourse surrounding digital classrooms, particularly PowerPoint presentations, as a dominant or limited educational tool. The arguments made by institutions in favor of PowerPoint presentations are becoming more and more forceful, thus it's critical to consider the values and ideologies in action. This study examines the institution's process of PowerPoint presentations and its teaching-learning activities through critical discourse analysis. Three public campus institution heads, three students, and a prospectus of these Campuses are chosen using the purposive sampling method to understand views on PowerPoint Presentations in teaching and learning activities within the classroom. The research finding shows that the paradigm shifts from traditional methods to more advanced digital approaches have resulted from the considerable transformation of educational practices brought about by digital technologies. PowerPoint presentations are becoming increasingly popular and compulsion, and they provide accessible and adaptable learning options. Research has shown that incorporating digital technologies improves student learning however it also interconnective the competitive policy of the campuses, and calls for a reassessment of educational approaches to meet the needs of the digital age.